A case in any case - Nilsson, Ulf, 1948- (Nilsson, Ulf, 1948- Kommissarie Gordon., 2017)
When Detective Gordon retires and Buffy is left alone at the police station, she hears strange noises and decides to call on Gordon to help her with the mystery.